The Edwards Valeo lifestents in the treatment and palliation of congenital heart disease in infants and small children. Issue 3 (17th February 2015) - Butera, Gianfranco; Giugno, Luca; Basile, Domenica; Piazza, Luciane; Chessa, Massimo; Carminati, Mario
<x xml:space="preserve">Abstract</x> Background Intravascular stenting is the procedure of choice in the treatment of vascular stenoses. However, in infants and small children large sheaths are needed, and adult‐size stents cannot be implanted. The Valeo Biliary Lifestent (Edwards Lifesciences Irvine, CA) is low profile and can be dilated up to 18‐20 mm. We aimed to report on early and mid‐term results with the use of Valeo stents in infants and children with congenital heart disease. Methods Twenty‐five subjects were treated in our experience. Mean age and weight were 39 ± 35 months (range 1–132) and 10.4 ± 6.7 kg (range 3–30), respectively. Two groups of patients were: Group A: patients with pulmonary artery stenosis (21 subjects); Group B subjects in whom stenting was applied in other vessel or heart sites (four subjects). Results A total of 35 stents were successfully used. Fluoroscopy time was 32 ± 11 min. No intra‐operative death or hospital mortality was recorded. Stent post dilatation was performed in nine patients. The incidence of complication was 12% (3/25) (two subjects developed transient hypotension and bradycardia which required inotropic treatment, 1 patient developed mild lung bleeding). There was a significant improvement of angiographic appearance and RV pressure (RV/AO systolic pressure ratio before 1 ± 02 (range 0.8–1.5) versus after the procedure 0.6 ± 0.2 (range 0.4–0.9) P < 0.001). In group B stents were successfully implanted in aortic recoarctation, interatrial septum and in two modified BT shunts. At a median follow‐up of 18 months (range 1–24 months) results remained stable and no complications occurred. In particular no stent fractures were seen. Furthermore, redilation was performed safely and successfully in three subjecs up to 18 months after the first implantation. Conclusions In our series, Valeo Lifestents have proven to be effective and with low incidence of complication in various anatomical settings, in low weight infants and in early post‐operative course. Large series and longer follow‐up are mandatory. © 2015 Wiley Periodicals, Inc.